Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Moderasi (Bukti Empiris pada Perusahaan BUMN yang Terdaftar di BEI Periode Tahun 2021-2024) - Khariesma Putri Marisa; Hudi Kurniawanto (ProBank, 2025)
This study aims to examine and analyze the effect of financial performance on company value and to examine the role of Good Corporate Governance (GCG) as a moderating variable in this relationship. The objects of this study are state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) in the period 2021–2024, with a population of 27 companies. The sampling technique used is purposive sampling. Based on these criteria, a sample of 19 companies was obtained. This study uses quantitative data, with the data source being secondary data. The data analysis in this study uses simple linear regression analysis to test the first hypothesis and multiple linear regression analysis using moderation regression analysis (MRA) to test the second hypothesis. The results of the study on the first hypothesis using simple linear regression analysis indicate that financial performance projected by Return on Assets (ROA) has a significant influence on company value, while Good Corporate Governance (Independent Commissioners) does not moderate the relationship between Financial Performance Return on Assets and Company Value.